Losy życiowe małoletnich matek, byłych wychowanek placówek opiekuńczo-wychowawczych. Perspektywa biograficzna = Fate of underage mothers, former pupils of correctional facilities - Skowrońska-Pućka, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The topic of the empirical verification presented fragmentarily in this article is (too)early motherhood and the experience accompanying it. Both are part of life trajectory of young girls, former pupils of correcting facilities, who decide to undertake and fulfill the role of mother. The aim of the article is to present implications resulting from (too)early motherhood and their influence on the current educational, professional and relationship situation of the young mothers after they have left correctional facilities.
Keywords: nastoletnie macierzyństwo; placówka opiekuńczo-wychowawcza; konsekwencje (przed)wczesnego macierzyństwa; rodzina; teenage motherhood; correctional facility; consequences of (too)early motherhood; family